2010
DOI: 10.1007/s11590-010-0220-z
|View full text |Cite
|
Sign up to set email alerts
|

Using several advertising media in a homogeneous market

Abstract: We propose a variety of models to represent the joint effect of several advertising media on the demand for a product in a homogeneous market, and discuss the associated profit maximization problems. An advertising productivity function represents the combination of several media and, together with demand and advertising cost functions, determines the features of the associated profit problem. We distinguish between additive and nonadditive advertising productivity functions, then between smooth and nonsmoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Their study (Liu et al, 2012) encapsulated that credibility has a potential impact on online advertisement regarding consumer behavioral intentions. Several scholarly articles (Breuer et al, 2011;Sorato and Viscolani, 2011) addressed the time effect of different types of online advertisements for communication effectiveness through an extensive empirical study among consumers. Breuer et al (2011) and several other authors (Anbu and Mavuso, 2012;Gold et al, 2011;Ho et al, 2010) identified that different kinds of online/mobile advertising channelssuch as email, banner, short messaging service (SMS), and PCAhave different sustained (time dependent) effects on consumers.…”
Section: Category 6a: Effective Consumer Communication: Online or Mobmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study (Liu et al, 2012) encapsulated that credibility has a potential impact on online advertisement regarding consumer behavioral intentions. Several scholarly articles (Breuer et al, 2011;Sorato and Viscolani, 2011) addressed the time effect of different types of online advertisements for communication effectiveness through an extensive empirical study among consumers. Breuer et al (2011) and several other authors (Anbu and Mavuso, 2012;Gold et al, 2011;Ho et al, 2010) identified that different kinds of online/mobile advertising channelssuch as email, banner, short messaging service (SMS), and PCAhave different sustained (time dependent) effects on consumers.…”
Section: Category 6a: Effective Consumer Communication: Online or Mobmentioning
confidence: 99%
“…6: Amrahi et al, 2014; Barnes and Pressey, 2012;Constantinides, 2004;Fiorini and Lipsky, 2012;Forsythe et al, 2006;Granados et al, 2011;Hsieh et al, 2012;Huang, 2012;Ivanov, 2013;Lee et al, 2012;Li and Du, 2011;Michaelidou et al, 2011;Mihai et al, 2012;Papasolomou and Melanthiou, 2011;Saravanakumar and SuganthaLakshmi, 2012;Sayadi and Makui, 2014;Schimmenti et. al., 2013;Taylor and Strutton, 2011;Zheng and Ma, 2013 Category 6a: Anbu and Mavuso, 2012;Breuer et al, 2011;Breuer and Brettel, 2012;Gold et al, 2011;Ho et al, 2010;Liu et al, 2012;Sorato and Viscolani, 2011;Thomaidou et al, 2012;Trkulja, 2012;Xu et al, 2013 Marketing and communication channel; Consumer preferences for different web search tools and social networks.…”
Section: Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…in (Färe et al, 2004) and (Reynar et al, 2010), and from an optimization point of view in several papers going back to (Balachandran and Gensch, 1974) and more recently e.g. by (Sorato and Viscolani, 2011), (Nobibon et al, 2011) and (Sönke, 2012).…”
Section: Introductionmentioning
confidence: 99%